Shock Index as Simple Clinical Independent Predictor of In-hospital MACEs in NSTEMI Patients Presenting with Heart Failure - Handayani, Ahmad; Kaban, Kartika; Nasri, Marwan; Mukhtar, Zulfikri; Siregar, Abdullah Afif (The Indonesian Heart Association, 2017)
Background: Identification of Non-ST Elevation Myocardial Infarction (NSTEMI) patientsat higher risk of in-hospital complications is very important. Such identification will givecrucial information in determining treatment strategy especially for those come with heartfailure. One of the simple predictor for short term prognosis in acute coronary syndromeis shock index (SI), which is the ratio of heart rate over systolic blood pressure on admission.There had not been any study conducted to evaluate the use of SI in NSTEMI patientscome with heart failure. The aim of this study is to evaluate the SI compared with otherroutine clinical and laboratory examination as a predictor of in-hospital major adversecardiac events (MACEs) in NSTEMI patients presenting with heart failure.Methods: We performed a retrospective analysis of NSTEMI patients with heart failureadmitted to Haji Adam Malik General Hospital in Medan from January 2014 until July 2015.SI was calculated as the ratio of heart rate over systolic blood pressure on presentation.Patients presenting with cardiogenic shock were excluded.Results: There were 55 patients eligible in this study. In-hospital MACEs was found in 24patients (44%) compared with 31 patients (56%) without in-hospital MACEs. Patientswith in-hospital MACEs were older (60.6±10.8 vs. 57.2±7.9, p=0.178), had less historyof dyslipidemia [8(33%) vs. 19 (61%), p=0.032], faster heart rate (111.4±35.8 vs.96.5±24.3, p=0.032], higher GRACE score [139(98-187) vs. 120 (91-148); p=0.001],and higher SI [0.83(0.57-1.5) vs. 0.67 (0.38-1.27), p=0.013). SI >0.8 was the only independentpredictor of MACEs in NSTEMI patients presenting with heart failure (OR=4.3,CI=1.247-14.328, p=0.048).Conclusion: Beyond other routine examinations, SI is the only independent predictor ofin-hospital MACEs in NSTEMI patients presenting with heart failure.